St. John's Episcopal Church and hospital, Ketchikan, Alaska, August 1904 - Cobb, John N. (John Nathan), 1868-1930 (1904)
From John Cobb field notebook: St. John's Episcopal Church, Ketchikan. Hospital on the left. Aug. 1904